Patterns and Social Drivers of Code-Switching Among Yoruba Speakers in Nigeria: an Empirical Study - Raphael Idowu Ibiowotisi (Jurnal Sosial Sains dan Komunikasi, 2026)
This study examines patterns of code-switching among Yoruba speakers in Nigeria and explores the social factors that shape this widespread linguistic practice within contemporary multilingual settings. Specifically, it investigates the dominant forms of code-switching, the social variables influencing language choice among Yoruba–English bilinguals, and the communicative functions that switching serves in everyday interaction. A mixed-methods research design was adopted, combining quantitative and qualitative data collected from 200 participants in urban and semi-urban communities. Data were obtained through structured questionnaires, recorded natural conversations, and semi-structured interviews. The findings reveal that code-switching between Yoruba and English is pervasive, with occasional integration of Nigerian Pidgin, reflecting the multilingual character of contemporary Nigerian society. Both inter-sentential and intra-sentential code-switching emerged as the most frequent patterns. Rather than occurring randomly, language alternation is closely associated with social variables such as age, educational attainment, occupation, and communicative setting. The analysis further shows that speakers use code-switching strategically to negotiate identity, express prestige, accommodate interlocutors, and adapt to the linguistic expectations of particular social domains. Younger and more highly educated participants displayed greater flexibility in alternating between Yoruba and English, often using English to project modernity, professional identity, and upward social mobility. By contrast, older speakers showed a stronger preference for Yoruba, particularly in culturally significant and interpersonal interactions. Beyond reflecting bilingual competence, code-switching functions as an important pragmatic resource for emphasis, clarification, rapport building, and effective communication in multilingual discourse. The study therefore argues that code-switching should not be viewed as evidence of linguistic deficiency but as a socially meaningful and communicatively effective practice arising from sustained language contact. By contributing fresh empirical evidence from the Yoruba speech community, the study advances discussions on bilingualism, language contact, and linguistic hybridity in postcolonial Africa. It also offers insights that are relevant to language planning, multilingual education, and ongoing efforts to promote the vitality of indigenous Nigerian languages in an increasingly globalised linguistic environment.